Analisis Kinerja Jasa Lingkungan Penyedia Air dan Daya Dukung Air Kabupaten Ketapang Secara Spasial : Penelitian - Alfajar, Gilang; Adi Kuntoro, Arno; Laili Yasinta, Nur; Irfie Lutfia Aulia, Rahman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The availability of sufficient and good quality water is essential for the survival of both humans and the environment. However, in several regions, water resources have been declining due to various factors such as land use changes and excessive exploitation. Ketapang Regency, located in West Kalimantan Province, is one of the areas facing challenges related to water carrying capacity. This study was conducted to spatially analyze the water carrying capacity in Ketapang Regency. The method used is descriptive with a spatial approach. The data used in this study are secondary data, and the analysis techniques include the water vulnerability index and descriptive analysis. The results indicate that most areas in Ketapang Regency exhibit a high level of water vulnerability. This finding highlights the urgent need for better water resource management to minimize the risk of water shortages and negative impacts on both the environment and society. This research is expected to serve as a reference for decision-making in water resource management policies in Ketapang Regency.